Impact of Intervention on Innovative Strategies to Optimize Mental Health of Farmers - M.S., Patil,; P.B., Khadi (Indian Journal of Extension Education, 2018)
An experimental research was conducted to know the impact of intervention on innovative strategies to optimize mental  health of farmers of experimental group in comparison with control group. The total sample of the study comprises 475  farmers. Depression Anxiety Stress Scale developed by Lovibond & Lovibond (1995), Stress- Perceived Stress Scale  developed by Sheldon Cohen, (1994), Beck's Depression Inventory (2004) were used to assess mental health problem  such as anxiety disorder and depression, stress and depression level among farmers. Results revealed that the effect  scores (Pre test - Post test I) on stress: the farmers of experimental group showed significant decrease in stress score  compared to the scores of control group. However, the decrease in the retention scores (Post test I – Post test II) was found  to be less among experimental group. In depression, the effect scores of the farmers of experimental group showed  significant decrease (14.83) in the depression level compared to the farmers of the control group (6.32). The significant  decrease in the retention scores was also found among experimental group. In mental health problems, the decrease in the  effect scores of experimental group was found to be -23.00 and for control it was only -7.88, which showed significantly  high decrease in the experimental group. The difference in the retention scores was also more in experimental group.  However, interactionary effect was found to be significant with both tests and groups. These results highlighted the need  for intervention on familial aspects to enhance their overall mental health status.
Keywords: Coping strategies; depression; farmers; intervention; mental health; stress